Mobile Tourist Guide â?? An Intelligent Wireless System to Improve Tourism, using Semantic Web - El-Sofany, Hosam; Abou El-Seoud, Samir (International Journal of Interactive Mobile Technologies (iJIM), 2011)
With the recent advances in Internet and mobile technologies, there are increasing demands for electronic access to tourist information systems for service coordination and process integration. Mobile computing and mobile devices are used to implement various tourist services (e.g. electronic tourist guides, digital interactive maps, and tourist e-commerce transactions). However, due to disparate tourist information and service resources such as airlines, hotels, tour operators, it is still difficult for tourists to use them effectively during their trips or even in the planning stage. Neither can current tourist portals assist tourists proactively. To overcome this problem, we propose the analysis, design, and implementation of the â??Mobile tourist guide" system, that access through wireless devices and use Semantic Web technologies for effective organization of information resources and service processes. The proposed system provides the users with various services such as: 1) displaying the shortest path between the sources and destinations the visitors specify, 2) displaying general information of shops, newest events of the plaza and shops, 3) provides service of hotel, restaurant and cinema-ticket reservations, 4) provides user-friendly administration service. The Admin can manage the position, blocking path details, general information of hotel, restaurant, shops and plaza, and reservation details via web browser without changing the framework of the system. The system prototype has been developed on the top of Java 2 Micro Edition which offers an ideal platform for the development of full-fledged, interactive and portable applications tailored for resource constrained mobile devices. The paper presents our development experiences and highlights its main advantages and limitations in relation to the implementation of such kind of applications.